Complex cellular environments imaged by SERS nanoprobes using sugars as an all-in-one vector. Issue 45 (28th October 2021) - Gomes, Maria C.; Chen, Juan; Cunha, Angela; Trindade, Tito; Zheng, Gang; Tomé, João P. C.
Abstract : Raman spectroscopy coupled with confocal microscopy offers an alternative bioimaging technique overcoming limitations associated with sensitivity, tissue penetration and image resolution. Abstract : Raman spectroscopy coupled with confocal microscopy offers an alternative bioimaging technique overcoming limitations associated with sensitivity, tissue penetration and image resolution. Allied to the surface-enhanced Raman scattering (SERS) properties of gold nanoparticles (AuNP), we designed SERS nanoprobes with enhanced properties and straightforward application as bio-labelling agents for gliomas. The ensuing nanoprobes coated with simple sugar units (galactose or glucose) allowed assessing information about their intracellular localization (vesicular structures), with impressive sensitivity towards complex environments and proved the ability to overcome biological auto-fluorescence and high penetration in tissues. We validate the use of sugars as an all-in-one vector (Raman reporter, conferring high stability, biocompatibility and affinity to glioma cells) as imaging agents using an impressive technique.